Extremist propaganda in social media: a threat to homeland security - Erbschloe, Michael (CRC Press, Taylor & Francis Group, 2019)
chapter 1 A Framework to Analyze the Impact of Social Media Propaganda on Intolerance, Extremism, and Radicalization in Society -- chapter 2 Social Media Propaganda and the Political Electoral Process -- chapter 3 Government Institutional Response to Social Media Propaganda, Extremism, and Radicalization -- chapter 4 Military Response to Social Media Propaganda-Driven Extremism and Radicalization -- chapter 5 The Impact of Social Media Extremist Propaganda on Law Enforcement -- chapter 6 The Corporate Extremist Propaganda Machine -- chapter 7 Extremist Propaganda and Recruitment Targeting Youth -- chapter 8 Electronic Aggression or Free Speech -- chapter 9 Countering Extremist Anti-Science Propaganda -- chapter 10 Observations on the Distribution of Extremist Propaganda -- chapter 11 Ten Reasons Why Propaganda Works.